PENGEMBANGAN MODUL TERAPI AL-QURAN SURAH ALI-IMRAN : 139, SURAH FUSHSHILAT : 30 DAN SURAH AL-ISRA : 70 UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA DI SMP NEGERI 1 PEKANBARU - Sumarni, Sumarni; Saam, Zulfan; Umari, Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study determines to develop an Islamic therapy module to increase self-confidence in terms of physical / appearance aspects, preliminary aspects, content aspects, task aspects and summary aspects. The method used is research and development (R&D). The steps used are (1) potential and problems, (2) data collection, (3) product design, (4) design validation and (5) tested design. Instrument in this study a questionnaire in the form of a validation sheet, while the validators in this study were 2 BK lecturers and 2 BK teachers. The results show that the Islamic therapy module is compiled to increase self-confidence in terms of 5 aspects, namely (1) the quality of the physical / appearance aspects was 83.75% in the